Where are you going, electroanalysis? - Štulík, Karel (Univerzita Pardubice, 2010)
A very general (and subjective) view is provided concerning the present state and possible development of electrochemical approaches to analysis. Both topics of interest are considered in the framework of the general character of contemporary science.
Keywords: electroanalysis; measuring techniques; application fields; present state; prospects